"Double Reflection": A Practical Approach to Teach Patient‐Doctor Communication in Oncology. (21st August 2013) - Mannhardt, Ann‐Kristine; Ogbonnaya, Lucky; Gieseler, Frank
Abstract : An individual‐focused approach is proposed to teach effective patient‐doctor communication in oncology as a factor relevant to treatment decision making for advanced cancer. The "double reflection" method unveils the importance of empathetic elements and will help students improve their communication skills.